STRATEGI PENGEMBANGAN PEMASARAN PUPUK KOMPOS ORGANIK PADA YAYASAN PEMILAHAN SAMPAH TEMESI, KABUPATEN GIANYAR - Paksi Bali Dewa; I Made Sudarma; I Dewa Putu Oka Suardi (Universitas Udayana, 2019)
The waste problem is not only related to the production and its transportation, but also concerning the sorting of organic and non-organic types. Temesi landfills in Gianyar Regency through the Yayasan Pemilahan Sampah Temesi (YPST) has a waste sorting activity to be used as a more economical product, namely compost fertilizer